DUAL OF A FUZZY MEASURE- A NOTE - SIVAKUMAR, P. S.; SADHANAA, D. (International Journal of Mathematical Archive, 2018)
The objective of this paper is to construct the dual of the fuzzy measure. For this purpose conjugate of the fuzzy measure is formulated and checked for duality. Self dual fuzzy measures exist. Example of self dual is given. The properties of the fuzzy measure are formulated. The same properties hold good for the conjugate fuzzy measure also.